Sweet air : modernism, regionalism, and American popular song - Comentale, Edward P. (Music in American life., 2013)
This book rewrites the history of early twentieth-century pop music in modernist terms. Tracking the evolution of popular regional genres such as blues, country, folk, and rockabilly in relation to the growth of industry and consumer culture, the author shows how this music became a vital means of exploring the new and often overwhelming feelings brought on by modern life.